Differences in Serum Blood Sugar Levels that were Directly Checked and Delayed for 1 Hour at Room Temperature using a Gel Separator Vacuum Tube - Oktaviyani , Tariska Inka; Asdinar, Asdinar; Adam, Adam; Islawati, Islawati (CV. Science Tech Group, 2025)
Blood sugar testing is essential for diabetes management and should be fast, accurate, and affordable. This study aims to determine the difference in blood sugar levels between immediate and delayed (1-hour) serum examinations using vacuum gel separator tubes at Prof. Dr. H. M. Anwar Makkatutu Bantaeng Hospital. An observational laboratory research with a comparative quantitative design was conducted on 23 purposively selected patients undergoing routine check-ups, without a history of diabetes mellitus. Blood samples were analyzed immediately and after a 1-hour delay at room temperature. Results showed that in immediate examinations, blood sugar levels ranged from 79 to 161 mg/dL, with a mean of 109.26 mg/dL. In delayed examinations, levels ranged from 81 to 164 mg/dL, with a mean of 111.74 mg/dL. Statistical analysis revealed a significant difference between the two groups (P < 0.05). The findings suggest that delaying blood sugar testing by 1 hour can lead to measurable changes in serum glucose levels, emphasizing the importance of timely sample processing in clinical settings.